Chocolate and Health: Friend or Foe? - Emilio Jirillo (Frontiers Research Topics, 2018)
In the ancient past, cocoa has been appreciated as a high-calorie food to boost energy in soldiers and for its undefined medicinal and mystical properties. During other times, chocolate has been considered as the forbidden "food of God": a treasure of pleasure for the mind and the soul. The overall perception of the consumer for chocolate was of a "charming" and appealing food with lots of negative aspects related to high sugar content leading to consider chocolate as "junk food" for its "obesigen" calories. Recently, in association with the renewed interest of nutrition science in alternative source of health-promoting foods and ingredients, a large body of research has been conducted to unravel the pro and cons of cocoa in relation to human health. Epidemiological evidences indicate that cocoa consumption helps preventing cardiovascular disease for its high content in bioactive flavonoids. Clinical trials show that chocolate consumption might improve vascular function, decreasing platelet aggregation and display an antioxidant and anti-inflammatory effect. The putative protective action of cocoa seems to be multi-factorial and involving different aspects of vascular, antioxidant and endothelial function. However, the mechanism(s) that account for the benefits of cocoa it is still unclear. The aim of this Research Topic is therefore to provide the reader with an objective picture of the state of art on the association between cocoa and health, mainly through the evidences of human trials; overwhelmingly considered the golden standard for nutritional science. The Research Topic will cover the analysis of the manufacturing processes of the chocolate and the antioxidant effects in humans as well as the majority of the putative health effects of chocolate and cocoa, such as anti-inflammatory properties, effect on immunity, platelet aggregation, blood pressure, endothelial function and cognitive behavior. Unraveling the functional properties of cocoa will help to understand if the 'food of God' is a primordial gift for the health of mankind.